The metatext of culture and the limits of translation in Ngũgĩ wa Thiongo’s Devil on the Cross (1982) - Kamau, Nicholas Goro (Research Journal in Advanced Humanities, 2022)
This paper examines Ngũgĩ’s translation of his first Gĩkũyũ language novel Caitaani Mũtharaba-inĩ into English, with a view to showing how the author translates Gĩkũyũ culture and idiom into English. Starting from the premise that the act of literary creation inevitably starts within a culture, the paper proceeds from the position advanced by Nadine Gordimer that literature in indigenous African languages must be confident that it can connect with the literary culture of the outside world on its own terms (2003, p. 7). The paper goes further to shows how Ngũgĩ attempts to ensure that his translation of the novel into English does not become complicit with the linguistic and cultural hegemony of the English language while at the same time making sure that the translated text is intelligible to the English reading public. This shows the primacy of the indigenous gnosis, its language and worldview in Ngũgĩ’s practice as a writer and translator and the foremost advocate of writing in African indigenous languages. The paper comes to the conclusion that Ngũgĩ’s translation of the novel into English as Devil on the Cross makes deliberate efforts to resist the absorption of the indigenous culture and language by English.